The The Effect of Using Wordwall Media to the Students’ Learning Achievement of 11th Grade At SMAN 1 Kramatwatu - ARDINA, ESTER MINKA (JEDLISH : Journal Of Education and English Language Teaching, 2024)
This study aimed to examine the examine the effect of word wall media to students’ learning achievements at SMA N 1 Kramatwatu. This study used a quasi experimental method with a nonequivalent contol group design. The population in this study was eleventh grade studens’ at SMA N 1 Kramatwatu, with two classes as sample, namely class XI3 consisting of 35 students’ as experimental class, and class XI4 consisting of 35 students as the control class. The data collection technique involved the use of test consisting of 20 multiple-choice questions. For pretest hypothesis testing, a t-test was used, and the results showed a value of t-count = 0.114, and t-table =1.994 indicating there was no difference between the experimental and control class before experiment. For post-test hypothesis testing, the test result showed a value of t-count = 2.252 and t-table = 1.994, indicating there was difference between the experimental and control class after the experiment. This shows that the used of wordwall media has a significant effect towards the students’ learning achievement of class XI of SMA N 1 Kramatwatu.